Association between clinical and demographic factors on cerebral amyloid angiopathy and Alzheimer dementia: Human neuropathology/amyloid. (7th December 2020) - Mousavi, SeyedAli; Hirsch‐Reinshagen, Veronica; Mackenzie, Ian R.; Ducharme, Blake; Chatterjee, Atri; Hsiung, Ging‐Yuek Robin
Abstract: Background: Cerebral amyloid angiopathy (CAA) is common in age‐related dementia. However, the relationships between severity of CAA and other demographic, and pathological factors are unclear. Therefore, we will examine them in this case series. Method: We reviewed records of patients with dementia who underwent autopsy at the UBC Hospital Clinic for Alzheimer's disease between 1994 and 2017 and selected cases in which CAA is identified with AD and compared them to cases with AD pathology only. We excluded cases with other coexisting pathologies (i.e. Lewy Body, TDP‐43). CAA was evaluated with Congo Red stain and rated semi quantitatively. We examined a subset in which APOE genotype was also available. Relevant clinical and pathological characteristics were compared by chi‐square test, ANOVA and logistic regression. Result: 225 cases (120 females) were included: 42 no CAA, 99 mild, 57 moderate, and 27 severe. APOE genotype was available in 70 cases (30 females). There was no significant association between sex ( p = 0.316), and APOE genotypes ( p = 0.799) with severity of CAA. History of dyslipidemia ( p = 0.004), current alcohol intake ( p = 0.016) and lower level of education ( p = 0.001) were associated with greater severity of CAA. Episodic memory ( p = 0.044) and visuospatial problems ( p = 0.049) were significantly associated with increased severity of CAA. Diffuse and lobar atrophy ( p = 0.013) and ventricular dilatation ( p = 0.026) were more prominent in severe CAA cases. There was a positive correlation between deep nuclear atrophy ( p < 0.001) and substantia nigra paleness (P = 0.013) with moderate CAA. There were also significant associations between severity of CAA with frequency of the microscopic hemorrhage ( p < 0.001), lacunar infarcts ( p = 0.011), and arteriosclerosis ( p = 0.003). Conclusion: Greater severity of CAA is associated with certain clinical and pathological factors including dyslipidemia, alcohol intake, lower education, and presence of lacunar infarcts. Sex and APOE genotype do not appear to have any significant influence on the severity of CAA in AD. Further studies will help to confirm these potential modifiable risk factors for CAA in AD.